PENGARUH MODEL POE PADA MATERI KOLOID TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Ratih Yuliasih; Husna Amalya Melati; Rahmat Rasmawan (Universitas Tanjungpura, 2017)
Abstract The purposes of this research were to know the difference between the critical thinking skills of the students of class XI MAN 1 Pontianak which is taught using predict-observe-explain (POE) learning and is taught using conventional model and know the influence of predict-observe-explain (POE) learning model on students' critical thinking skills on colloid subjects. The form of this research is Quasi Experiment with research design